HEART RATE VARIABILITY IN PAROXISMAL ATRIAL FIBRILLATION BEFORE AND AFTER CATHETER ABLATION AT AN EXAMPLE OF CLINICAL CASE - Streliana, I. A.; Brynza, M. S.; Volkov, D. E.; Lopin, D. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Changes in heart rate variability (HRV) before and after catheter radiofrequency ablation (RFA) of pulmonary veins in paroxysmal atrial fibrillation (AF) are considered at an example of clinical case. Initially low HRV in patients after ablation halved, which can lead to increased frequency and extension of AF paroxysms. In the accompanied medication, which included bisoprolol, valsartan, atorvastatin and rivaroxaban, to increase HRV were proposed increasing the dose of bisoprolol or search for more effective beta blocker. The initial low TP spectrum of HRV in patients after RFA reduced by half, which can lead to increased frequency and extension of paroxysmal AF [1–2, 4]. In the accompanied medication, which included bisoprolol, valsartan, atorvastatin and rivaroksaban, to increase HRV were proposed increasing of bisoprolol dose and with no results – search for another beta blocker.